Impact of sleep-disordered breathing and its treatment on children with primary nocturnal enuresis (Swiss Medical Weekly, 2011)
OBJECTIVES: To determine the prevalence of primary nocturnal enuresis in children, to define the possible role of sleep-disordered breathing (SDB) related to adenotonsillar hypertrophy in enuresis, to explore the role of brain natriuretic peptide (BNP) levels in measuring the severity of SDB in enuretic children, and to evaluate the response to surgical interventions (adenotonsillectomy) in indicated enuretic patients. METHODS: Parental surveys of 5–10 year-old children were reviewed for SDB and enuresis. Children with SDB were clinically and radiologically examined. Plasma BNP levels were determined in 33 children with SDB and enuresis and in 30 otherwise healthy children of whom 15 had enuresis. RESULTS: A total of 15.3% of the studied children had primary nocturnal enuresis, and 47 children with enuresis (30.7%) had SDB. There was a downward trend of enuresis and SDB as age increased. There appeared to be an association between the frequency of enuresis, snoring and adenotonsillar enlargement. Plasma BNP concentrations were significantly higher among enuretic children. All enuretic children with SDB underwent surgical intervention (33 patients), and an improvement was observed in 29 children (87.8%). Among them, 15 were cured completely, and 12 made a significant improvement in the initial 3 months, but two made just a partial improvement over one year, and four did not show any improvement over one year follow up. All enuretic children with SDB who underwent surgery exhibited a significant reduction in daytime enuresis. CONCLUSIONS: The data suggests an association between nocturnal enuresis and adenotonsillar related SDB in children. Enuresis may add to the indications for surgical intervention in this group. Increased BNP levels may account for the increased prevalence of enuresis in context of SDB.